Achieving Pro-Poor Growth and Environmental Sustainability Agenda Through Information Technologies: As Right as Rain - Muhammad Imran; Khan Burhan Khan; Khalid Zaman; Mohammed Borhandden Musah; Elih Sudiapermana; Rahimah Embong; Zainudin Bin Hassan; Mohd Khata Jabor; Siti Nisrin Mohd Anis; Abdul Rashid Abdul Aziz (Springer Link, 2024)
Indexed by WOS/SCOPUS